Digital Public Relations to Improve Customer Relation: Netnography Study on @kai121 Account - Alifa Nur Fitri; Millata Hanifa (Jurnal Komunikasi, 2025)
This article discusses the application of Digital Public Relations (DPR) to improve customer relationships through a netnography study on the @kai121 Instagram account. In the digital era, the interaction between brands and consumers is increasingly influenced by social media platforms, especially Instagram. This interaction is a form of customer relations by KAI to communicate with its customers. This research aims to explore how Digital Public Relations strategies can create better engagement with customers, as well as analyze the content and interactions that occur on those accounts. The methodology used is netnography, which allows researchers to understand the social and cultural contexts of online interactions. The study results show that effective Digital Public Relations can create customer loyalty, increase satisfaction, and build a positive brand image. This finding is expected to provide insight for companies in formulating a better Digital Public Relations strategy in the digital era. The results of the study concluded that the use of social media, especially Instagram, has great potential in strengthening the relationship between KAI and customers. Customer relations through Instagram @kai121 can strengthen the relationship between KAI and customers. Active engagement, good image management, and responsiveness to customers are key elements in creating a mutually beneficial relationship. KAI has managed to establish a good relationship with customers, as evidenced by the many likes and comments as well as positive sentiment in comments. KAI uses the strategy of riding the wave, making activities, quizzes and give away. These findings provide a basis for companies to develop a more integrated customer relations strategy in the digital era.